Investigation and prediction of quality parameters of Gamasyab river using multivariate method of Canonical correlation analysis and time series - Maryam Sayadi; Mojtaba G.Mahmoodlu (Mashhad University of Medical Sciences, 2019)
Background and purpose: The present study was performed to investigate trend and prediction of changes in some quality parameters of Gamasyab river water using multivariate statistical methods and time series.   Materials and methods: In this research, the annual means of some qualitative parameters related to a 6-year statistical period in two Pol-Chehr and DoAb stations were used. At first, the factors controlling chemistry of Gamasyab river were determined using Ternary and Gibbs diagrams. Then, to determine a linear relationship between multidimensional variables, Canonical correlation coefficients were used. Finally, the changing trend of water quality parameters in next 5-years was predicted.   Results: At Pol-Chehr station, qualitative parameters show an upward trend except for pH. While at DoAb, all qualitative parameters show a downward trend except for Mg and SO4. Based on Ternary and Gibbs diagrams, water dominant facies are Ca-Mg-HCO3 and the main factor controlling water chemistry is water-rock reaction at both stations, respectively. Results showed that the chemical parameters of HCO3 and Mg at Pol-Chehr with canonical coefficients of 0.938 and 0.933 are in the first group and Na with coefficient of 0.845 is situated in the second category. While in DoAb station, chemical variables HCO3 and Ca with coefficients of 0.945 and 0.0789 are placed in the first group, and Na and Cl with the coefficients of 0.930 and 0.800 are in the second group, respectively. First and second group origins of canonical variables can be related to dissolution of limestone and evaporative deposits. Prediction results of the water quality parameters changes in Gamasyab river for the next 5 years showed that an increase in all the parameters except for pH at Pol-Chehr station. While except for Mg and SO4, all quality parameters will decrease at the DoAb station. Conclusion:Water-rock reaction is the most important factor affecting Gamasyab river water chemistry.   Document Type: Research article